Taqlīd Ngunya li muslimī Pegayaman bi Bali: Taṭbīq al-sharī‘ah al-Islāmīyah fī baldat al-Hindūs - Muhamad Arif (Studia Islamika, 2019)
The 19th-century orientalists assumed that Balinese religious identity was formed through opposition to Islam. But this article provides contrary evidence. In Bali, Islam is exposed through associative patterns of interaction with Hindu-Balinese society since the 17th century. The Ngunya Muslim Pegayaman tradition is one of the results of the interaction between Islamic culture and Hindu culture in Bali. This article attempts to analyze the tradition according to three perspectives. In a continuity perspective, this tradition is one form of cultural acculturation and at the same time, explains how the Hindu community well receives the Islamic community. In a convergence perspective, Ngunya is a creative idea in resolving social conflicts related to marital procedures. In a concentric view, although the tradition was adopted from the Hindu tradition, Pegayaman’s Islamic community still made Islamic teachings the main reference in the procedure of marriage.